Core–shell microencapsulation of curcumin in PLGA microparticles: programmed for application in ovarian cancer therapy. (12th November 2018) - Dwivedi, Pankaj; Yuan, Shuai; Han, Shuya; Mangrio, Farhana Akbar; Zhu, Zhiqiang; Lei, Fan; Ming, Zhang; Cheng, Lei; Liu, Zhongfa; Si, Ting; Xu, Ronald X.
Abstract: In our study, we have established a novel liquid-driven co-flow focusing (LDCF) process to fabricate curcumin (CUR)-loaded poly (lactic-co-glycolic acid) (PLGA) microparticles (CPMs). LDCF-CPMs of size 20.26 ± 2.37 μm have high encapsulation efficiency (>70%) and were intended for application in ovarian cancer by intraperitoneal (IP) administration. LDCF-CPMs have smooth surface with narrow size distribution and a core–shell structured verified by confocal microscopy which can be precisely controlled by changing the flow rates of focusing, outer and inner phases. The LDCF-CPMs reveal the physiochemical stability with sustained release profile corresponding to 95% CUR release over a period of 14 days in an in vitro release medium. Moreover, LDCF-CPMs were testified for cytotoxicity against SKOV-3 ovarian cancer cell lines and peritoneal delivery advantages by animal experiments. The pharmacokinetics of LDCF-CPMs in rats following IP injection shows slow systemic absorption with mean residence time (MRT) of 13.54 h in comparison with 9.82 and 6.74 h for SE-CPMs and free CUR, respectively. In addition, IP delivery of CUR can expose the ovarian tumour to higher concentration for a longer duration by programming the thickness of the shell. The study provides compelling evidence for LDCF-CPMs having high therapeutic opportunity in the treatment of peritoneal cancers, such as ovarian, that reside in the peritoneal cavity.